China's wind electricity and cost of carbon mitigation are more expensive than anticipated - Lam, Long T. (2016)
The success of China's transition to a low-carbon energy system will be key to achieve the global level of emissions reductions needed to avoid large negative consequences from climate change. China is undergoing an impressive build up of renewable capacity, in particular wind. Using data from the Clean Mechanism Development project database between 2004 and 2012, this study shows that while China made progress in bringing down the levelized cost of wind electricity and cost of carbon mitigation (CCM), serious grid-connection issues and high wind curtailment rates resulted in a levelized cost of wind electricity that is one-half to two times higher than expected, and a CCM that is four to six times higher. Sharp drop in electricity demand, utilization rate, and coal prices in recent years may lead to even higher results.